Հայերէնի տեսութեան եւ կիրառութեան հարցերը «Արարատ» ամսագրի էջերում - Համբարձումեան, Վազգէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Журнал «Арарат» в 1869—1909 гг. был выразителем церковно-христианской жизни Св. Эчмиадзина, и многих культурно-духовных начинаний. Он предоставлял свои страницы также для разных исследований по языку, языкознанию в целом. Журнал публиковал исследования по истории армянского языка, его применения, обучения и пропаганды, что способствовало развитию и совершенствованию литературного языка. Авторами были не только представители науки, но и духовные служители Армянской Апостольской Церкви. Besides being an exponent of the ecclesiastical-Christian life of Holy Etchmiadzin and its diverse initiations in cultural-spiritual activities, “Ararat” magazine was also an agency that published various studies on language and linguistics in general from 1869 to 1909. The magazine published studies on the history of the Armenian language, its use, teaching and propagation, which gave an impetus to the development and improvement of the literary language, and its authors were not only scholars, but also clergymen of the Armenian Apostolic Church.
Keywords: Հաղորդումներ; Լեզուաբանութիւն